The Dark Side of Escaping the Middle-Income Trap: A SAGE Study of Asian High-Income Countries - Dennis J. Snower (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
The experience of rapid economic growth and transition to high-income status in Asian countries has brought about significant improvements in material well-being and aggregate economic prosperity. This article examines the degree to which economic prosperity is the "great enabler" of social and environmental prosperity. We provide conceptual reasons why this is not necessarily the case and empirical evidence that the escape from the middle-income trap in three Asian high-income countries – Japan, Singapore and South Korea – was a mixed blessing, linked to challenges regarding social solidarity, personal and collective agency and environmental stewardship. Under these circumstances, traditional prescriptions for escaping the middle-income trap are insufficient. Without success in the social and environmental spheres, social fragmentation and environmental disruption is likely to occur, possibly leading to political instabilities, economic fragmentation and social conflict. This paper investigates this problem for the three Asian high-income countries, based on empirical measures of solidarity (S), agency (A), material gain (G) and environmental stewardship (E) that are consistent through time and across countries. On this foundation, policy recommendations are considered that are meant to run alongside the standard prescriptions to make the resulting package socially and environmentally acceptable.
Keywords: O10; O47; O53; I31; Q56; Q01; 330; middle-income trap; economic development; human flourishing; social cohesion; agency; environmental stewardship; growth; wellbeing